Efektivitas Cacing Tanah Pheretima hupiensis, Edrellus sp. dan Lumbricus sp. dalam Proses Dekomposisi Bahan Organik - Anwar, Ea Kosman (JOURNAL OF TROPICAL SOILS, 2009)
Effectivity of the Earthworms PheretimaÂ  hupiensis, Eudrellus sp. and Lumbricus sp. on the Organic MatterÂ  Decomposition Process (E.K. Anwar): The earthwormsÂ  are the one of soil faunaÂ  component inÂ  soil ecosystem have an important role in organic matter decomposition procces. The earthworm feedÂ  plant leafÂ  and plant matter up to apart and dissolved.Â  EarthwormÂ  metabolismsÂ  produce like faeces that mixed with decomposed organic matterÂ  mean vermicompost. The vermicompost fertility varies because of some kind of earthworm differ in â€œnicheâ€Â  and attitude. The experiment was to study the effectivity of earthwormÂ  on organic matter decomposition which has been conducted in Soil Biological and Healthy Laboratory and Green House of Soil Research Institute Bogor, during 2006 Budget Year. The three kind of earthworms i.eÂ  Pheretima hupiensis, Lumbricus sp. and Eudrellus sp. combined with three kind of organic matter sources i.e rice straw, trash andÂ  palm oil plant waste (compost heap). The result shows that the Lumbricus sp.Â  are the most effective decomposer compared to Pheretima hupiensis and Eudrellus sp. and the organic matter decomposed byÂ  Lumbricus sp. as followed:Â  market waste was decomposed of 100%, palm oil empty fruit bunch (compost heap) 95.8 % and rice straw 84.9%,Â  respectively. Earthworm effectively decreased Fe, Al, Mn, Cu dan Zn.